Exposure to Solar Ultra Violet among Taxi Drivers in Damghan Area in 2016: A Cross-Sectional Study - Alireza Dehdashti; Mahdieh Ghainy; Ghasem Askari; Gholamreza Ghaeiny (Iranian Journal of Health, Safety and Environment, 2018)
Ultraviolet emission from sun considered as a hazardous parts of optical waves. This study aimed at determining exposure to ultraviolet radiation among taxi drivers in Damghan. A cross-sectional survey was conducted on a sample of taxi drivers. Individual exposure to solar ultraviolet-A was assessed during day light working hours. Exposure was determined on the basis of radiation intensity and biologically cumulated standard erythema dose. Our findings showed that exposure was varied in terms of time and geographical sites. The exposure intensity ranged from 0.01 to 15.36W/m2 and from 1.42 to 28.7W/m2 inside and outside the vehicles, respectively. Drivers had the highest exposure from June till August (17.54W/m2). Results showed lower exposure in April, May, and September (12.34W/m2). Cumulative exposure based on erythema dose showed the highest value (41.0 SED) inside vehicle at 9-10 am intervals. Taxi drivers are exposed to significant ultraviolet radiation. Geographical situation and time caused variations in exposure. Future studies should focus on the health effects so that determine the risk of exposure more accurately.